Management Control Systems, Organizational Culture and Village Credit Institution Financial Performance - I Made Pradana Adiputra; Edy Sujana (The Indonesian Journal of Accounting Research, 2021)
This study aims to provide empirical evidence about the influence of misfit management control systems (levers of control) with organizational culture will negatively affect the financial performance of LPDs. This study uses a survey method (questionnaire) based on a sample of 149 LPD units in Buleleng Regency with purposive sampling criteria. The research respondents were all three LPD officers (penyarik, pemucuk and petengen) and one staff each from the credit and accounting department.. The research hypothesis suggests that each organizational culture orientation, namely clan, adhocracy, hierarchy and market shows a fit (through misfit values) with levers of control (belief, boundary, diagnostic and interactive control system) has a negative effect on LPD financial performance. The analysis technique uses OLS regression residual approach to testing the research hypothesis. The results showed that the hierarchical culture was able to have a fit (a small misfit value) with a management control system (levers of control) to influence the financial performance of the LPD.